SWEDES PUBLISHING IN ESTONIA UP TO THE END OF THE SECOND WORLD WAR - Reimo, Tiiu (Knygotyra, 2016)
The ethnic Swedish minority inhabited the islands and Western coast of Estonia for about seven centuries, from the end of the 13th century up to the end of the Second World War. The settlements in remote islands hindered the intercommunication and the development of cooperative movement. However, the national awakening movement which started in the 2nd half of the 19th century created the conditions for national self-determination and consolidation of the Swedish community. The schools with instruction in Swedish and libraries were opened, educational and cultural societies established and books in Swedish published. The book culture of the Estonian Swedes was varied and manifold. The number of Swedish publications in Estonia was not big and not all of the print production in Swedish was intended for the use to the Swedish community. A lot of library books and schoolbooks were also obtained from Sweden. As a counterbalance, a lot of books on Estonian Swedish settlements were published in Sweden by people who were engaged in Swedish schools or churches in Estonia.
Keywords: ethnic minorities; Estonia; Estonian Swedes; Swedish language; publishing; national awakening movement; book production